A new giant titanosaur sheds light on body mass evolution among sauropod dinosaurs. Issue 1860 (9th August 2017) - Carballido, José L.; Pol, Diego; Otero, Alejandro; Cerda, Ignacio A.; Salgado, Leonardo; Garrido, Alberto C.; Ramezani, Jahandar; Cúneo, Néstor R.; Krause, Javier M.
Abstract : Titanosauria was the most diverse and successful lineage of sauropod dinosaurs. This clade had its major radiation during the middle Early Cretaceous and survived up to the end of that period. Among sauropods, this lineage has the most disparate values of body mass, including the smallest and largest sauropods known. Although recent findings have improved our knowledge on giant titanosaur anatomy, there are still many unknown aspects about their evolution, especially for the most gigantic forms and the evolution of body mass in this clade. Here we describe a new giant titanosaur, which represents the largest species described so far and one of the most complete titanosaurs. Its inclusion in an extended phylogenetic analysis and the optimization of body mass reveals the presence of an endemic clade of giant titanosaurs inhabited Patagonia between the Albian and the Santonian. This clade includes most of the giant species of titanosaurs and represents the major increase in body mass in the history of Titanosauria.